Endoscopic injection sclerotherapy in the treatment of bleeding oesophageal varices in patients with portal hypertension due to alcohol-induced cirrhosis : an assessment of acute control of bleeding and prognostic factors predicting early variceal re - Krige, Jacobus Edmund Joubert (Department of Medicine, 2014)
Includes abstract. Includes bibliographical references (leaves 232-268).